KAJIAN BASIS DAN PRIORITAS DALAM SEKTOR PERTANIAN BAGI PEMBANGUNAN WILAYAH PESISIR BENGKULU - Suryanty, Melli; Sriyoto, Sriyoto; Yuliarti, Ellys (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
The objectives of this research were to identify agriculture subsectors that can be the sector basis for the region development, and give information about priority scale of agriculture subsectors development in Bengkulu region development planning. This research used the secondary data gained from time series data from year 2000-2011. Analysis methods used in this research were sector contribution, location quotient, and shift share analysis. The results of the research showed that fishery subsector gave significant contribution for Bengkulu City PDRB. Fishery subsector became the basis and main priority of the agriculture development in year 2000-2011. This was shown from the biggest contribution value, location quotient value was greater than 1, and positive shift share value. The main priority of agriculture sector development is fishery, livestock, food plant, and estate subsector.